Komunikasi Pemasaran Pengelolaan Air Terjun Sikulikap dalam Menarik Pengunjung Wisatawan di Kecamatan Berastagi - Fauzi, Muhammad; Riadi, Selamat (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
The development of business in the field of tourism objects is currently very rapid, giving rise to competition to attract tourists. Rapid changes in the business environment have forced tourist attractions to continue to be active and creative in developing existing tourist sites and continuously making updates regarding strategies in marketing them. This study aims to determine " Marketing Communication of Sikulikap Waterfall Management in Attracting Tourist Visitors in Berastagi District, Tanah Karo ". The method used in this research is descriptive qualitative. Data from observations, interviews, and documentation were analyzed using descriptive analysis techniques. there were 6 resource persons, namely the manager of tourist attractions and tourists. The research location is in Sikulikap Waterfall, Berastagi. The results of this study are that tourism managers in implementing marketing communication strategies in attracting tourists, including three activities, including promotion activities through social media such as Instagram, and Instagram social media is quite effective as a marketing communication strategy in increasing the interest of visitors to Sikulikap Waterfall.